Traffic Modeling in PLC Networks using a Markov Fluid Model with Autocorrelation Function Fitting - Rocha, F.G.C.; Santos, C.B.; Vieira, F.H.T. (Trends in Computational and Applied Mathematics, 2011)
In this paper, we present an analysis of VoIP (Voice over IP) traffic and data transfer using PLC (PowerLine Communications) network. We propose a model based on MMFM (Markov Modulated Fluid Models) for data and VoIP traffic in PLC networks. Simulations and comparisons were carried out to verify the efficiency of the proposed traffic model over the Poisson and MMPP (Markov Modulated Poisson Process) models.